IMPLEMETASI PEMBELAJARAN BERBASIS PROYEK PADA BIDANG KEJURUA - Sofyan, Herminarto (Jurnal Cakrawala Pendidikan, 2016)
Vocational education is oriented to the formation of professional competency. Such competency has to be supported by nn1~':l't1"0 abilities, the acquisition these abilities ne'ed comprehensive learning experiences. Project- a making learning experiences more interesting and meaningful to university students, or, those undergoing transitional training when entering a field ofwork~ The project-based learning model helps learners (1) to learn hefty and meaningful use of knowledge and skill built through assignments and works, (2) to increase knowledge through curricular activities and the execution ofopen-ended planning or investigation, and (3) to build knowledge through real-world experiences and inter-personal cognitive negotiations conducted in an atmosphere of collaborative work. Project-based learning enables learners to learn more actively. The instructor, or, anyone in charge of the instructional process, stands encouragingly behind learners, who makes the initiatives. The instructor facilitates learners' projects and evaluates each project in terms of its meaningfulness in and application on their daily life. Outcomes during the project represent results that can be measured authentically by the instructor in the learning process. So, in project-based learning, though not giving training activeiy and directly, the instructor still has a role, as learning helper, facilitator, and partner who understands students' think